Servant leadership for higher education : principles and practices - Wheeler, Daniel W. (Hoboken, N.J. ; San Francisco, Ca : John Wiley & Son, Inc., 2012)
This practical book places an emphasis on principles and strategies to address issues. It is based on research and best practice. Organised around ten principles of servant leadership and how these principles apply to common issues faced in departments and institutions of higher education.